Multicriteria Scheduling Problems to Minimize Total Tardiness Subject to Maximum Earliness or Tardiness - Abdullah, H. F (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Scheduling problems have been treated as single criterion problems until recently. Many of these problems are computationally hard to solve three as single criterion problems. However, there is a need to consider multiple criteria in a real life scheduling problem in general. In this paper, we study the problem of scheduling jobs on a single machine to minimize total tardiness subject to maximum earliness or tardiness for each job. And we give algorithm (ETST) to solve the first problem (p1) and algorithm (TEST) to solve the second problem (p2) to find an efficient solution.